Modulation of aryl hydrocarbon receptor activity by halogenated indoles - Vrzalová, Aneta; Vrzal, Radim; Nádvorník, Petr; Šebela, Marek; Dvořák, Zdeněk (Bioorganic & medicinal chemistry, 2024)
The aryl hydrocarbon receptor (AhR) is a cytosolic ligand-activated transcription factor integral to various physiological and pathological processes. Among its diverse ligands, indole-based compounds have garnered attention due to their significant biological activity and potential therapeutic applications. This study explores the activation of AhR by structurally diverse halogenated indoles. We evaluated the transcriptional activity of AhR and cell viability in the human LS174T-AhR-luc reporter cell line. Among the tested compounds, 4-FI, 7-FI, 6-BrI, 7-BrI, 6-Cl-2-ox, 5-Br-2-ox, and 6-Br-2-ox activated AhR in a concentration-dependent manner, displaying high efficacy and potency. Molecular docking analysis revealed moderate binding affinities of these compounds to the PAS-B domain of AhR, corroborated by competitive radioligand binding assays. Functional assays showed that halogenated indoles induce the formation of AhR-ARNT heterodimer and enhance the binding of the AhR to the CYP1A1 promoter. Additionally, 4-FI and 7-FI exhibited anti-inflammatory properties in Caco-2 cell models, highlighting their potential for therapeutic applications. This study underscores the significance of the type and position of halogen moiety in indole scaffold, suggesting their potential as candidates for developing therapeutics drugs to treat conditions such as inflammatory bowel disease via AhR activation.
Keywords: Cell Survival; indoly; Aryl hydrocarbon receptor; Cytochrome P-450 CYP1A1; Humans; cytochrom P-450 CYP1A1; receptory aromatických uhlovodíků; simulace molekulového dockingu; Indoles; Structure-Activity Relationship; halogenace; vztahy mezi strukturou a aktivitou; Dose-Response Relationship, Drug; Molecular Docking Simulation; Inflammation; lidé; molekulární struktura; Molecular Structure; Halogenation; Receptors, Aryl Hydrocarbon; transkripční faktory bHLH; vztah mezi dávkou a účinkem léčiva; Indole derivatives; Halogen; viabilita buněk; Basic Helix-Loop-Helix Transcription Factors